Relasi Kuasa Dan Dinamika Isi Media Studi Ekonomi Politik Media Di Metro TV Pada Program Metro Siang - Muhammad Wahdan; Dessy Linda; Bachtiar Febriana (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2023)
The media is a public facility that functions to meet the public's need for information and is a pillar of democracy. However, in the industrial structure, the media is no longer seen based on its use value, but is focused on the exchange rate in obtaining economic benefits. The media and the press as the 4th pillar of democracy and tools of social control, their independence is continuously stripped by economic and political interests. The purpose of this study is to determine the power relations and dynamics of media content in the study of the political economy of media on Metro TV in the Metro Siang program. The research method uses a qualitative descriptive research type using an approach to the study of political economy. Data collection techniques for primary were through interviews with Metro Siang program producers on Metro TV, media experts, and secondary data through observation and literature on Metro TV. The results of this study can be concluded that Metro TV as a media corporation cannot avoid intervention by the interests of the owners of capital and power. Political Economy and Power Relations are two things that a media corporation like Metro TV must continue to play properly in order to continue to win the competition between media.